2018
DOI: 10.1021/acsmedchemlett.8b00517
|View full text |Cite
|
Sign up to set email alerts
|

Improved Selective Class I HDAC and Novel Selective HDAC3 Inhibitors: Beyond Hydroxamic Acids and Benzamides

Abstract: The application of class I HDAC inhibitors as cancer therapies is well established, but more recently their development for nononcological indications has increased. We report here on the generation of improved class I selective human HDAC inhibitors based on an ethylketone zinc binding group (ZBG) in place of the hydroxamic acid that features the majority of HDAC inhibitors. We also describe a novel set of HDAC3 isoform selective inhibitors that show stronger potency and selectivity than the most commonly use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…While HDACi effects on GF activation require further characterization with regards to the involvement of epigenetic and non epigenetic mechanisms, and should be studied in detail also in gingival epithelial cells ( Yin and Chung 2011 ), the results presented here provide strong evidence that HDAC3 acts as a crucial regulator of inflammatory mediator expression. Our data suggest that HDACi, in particular selective HDAC3 inhibitors ( Bresciani et al 2019 ), may ameliorate the excessive inflammatory response of gingival cells to periodontal pathogens, and their application could be clinically beneficial as an adjunct to the conventional treatment of periodontitis.…”
Section: Discussionmentioning
confidence: 88%
“…While HDACi effects on GF activation require further characterization with regards to the involvement of epigenetic and non epigenetic mechanisms, and should be studied in detail also in gingival epithelial cells ( Yin and Chung 2011 ), the results presented here provide strong evidence that HDAC3 acts as a crucial regulator of inflammatory mediator expression. Our data suggest that HDACi, in particular selective HDAC3 inhibitors ( Bresciani et al 2019 ), may ameliorate the excessive inflammatory response of gingival cells to periodontal pathogens, and their application could be clinically beneficial as an adjunct to the conventional treatment of periodontitis.…”
Section: Discussionmentioning
confidence: 88%
“…Fetal bovine serum, penicillin/streptomycin, glutamine, HEPES, fungizone, deoxyribonuclease I, and Hoechst 33342 were from Invitrogen (Thermo Fisher, Monza Italy Fluorescein isothiocyanate-labelled FITC-dextran 40, dimethyl sulfoxide (DMSO), lucifer yellow, rhodamine-123, kynurenic acid, elacridar (GF120918), Y-27632 (ROCK inhibitor), and triton X100 were purchased from Sigma-Aldrich, Milan, Italy, and 8% paraformaldehyde aqueous solution was from Electron Microscopy Sciences (Hatfield, PA, USA). CHDI compounds, denoted cp (A to J) and histone deacetylase (HDAC) inhibitor (cp K) were synthesized as previously described [10,11].…”
Section: Reagentsmentioning
confidence: 99%
“…We tested in our model a class I selective human HDAC inhibitor (CpK, Figure 7B), a preclinical development candidate that demonstrated proof-of-concept in an mdx mouse model for Duchenne muscular dystrophy and previously profiled in the porcine model [10]. This 2-methoxyquinoline derivative showed a medium permeability in both models, although the MPO score (a drug likeness central nervous system multiparameter optimization) is less than 3.8, slightly lower than the cut-off of 4 for probable permeable compound.…”
Section: Drug Candidates Permeability Measured In Hipsc-bmecsmentioning
confidence: 99%
“…Regardless of the clinical success, the present trend in this field is equally aligned towards the development of both the classes of inhibitors. An obvious explanation to this is the evidenced susceptibility of hydroxamic acids to glucuronide conjugation leading to inactivation and off-targeting whereas some explorations reported that aminoanilides are less prone to glucuronide metabolism and are endowed with high efficacy possibly due to their slow, tight binding and slow disassembling with HDACs [190,191,[363][364][365][366][367][368]. Another notable variation between the two classes can be observed in their enzymatic inhibitory profile as pan HDAC inhibition and selective HDAC 6 inhibition is mostly exerted via use of hydroxamic acid based HDAC inhibitors while class I HDAC selectivity is usually attained via the fabrication of aminoanilides.…”
Section: Isoform Selective Inhibitors: Employing a Structural Template To Furnish Selective Isoform Inhibitors Of The Enzymesmentioning
confidence: 99%